Study on immobilization of composite pollutants in antimony mining areas by target-enriched sulfate-reducing bacteria from antimony tailings - Zhu, Xuezhe; Zhou, Yupin; Zhang, Mingjiang; Yan, Xiao; Liu, Xingyu; Dou, Zhihe (Frontiers in Microbiology, 2025)
Remediating composite pollution in antimony mining areas, characterized by coexisting anionic metalloids (Sb, As) and cationic heavy metals (e.g., Pb, Cd, Cu, Zn), remains a significant challenge. This study demonstrates the effective immobilization of these complex pollutants using target-enriched sulfate-reducing bacteria (SRB) in heavy metal pollution remediation research. Indigenous SRB were enriched from antimony tailings and their application in remediating typical composite-polluted wastewater and tailings in antimony mining areas. The SRB community enriched in modified Postgate medium was dominated by the genus Clostridium, confirming the successful enrichment of functional sulfate-reducing microorganisms. Results of nutrient optimization showed that the optimal nutrients were 2.0 mL/L sodium lactate (carbon source), 1.2 g/L yeast extract (nitrogen source), and 0.5 g/L K2HPO4·3H2O (phosphorus source), and the corresponding medium enhanced SRB activity, increasing the Fe2+ immobilization rate to >90%. In simulated wastewater from antimony mining areas, SRB effectively immobilized various pollutants with immobilization rates of 97.9% for Sb, 82.8% for As, 91.7% for Pb, 99.7% for Cd, 99.5% for Cu, and 99.8% for Zn. Characterization via SEM-EDS, XRD, and FT-IR revealed that immobilization products were primarily composed of heavy metal sulfides, carbonates, hydroxides, and microbial extracellular polymeric substances (EPS). Biological tissues were also involved in the heavy metal immobilization process. For antimony tailings, Zn was effectively remediated whereas Sb and As exhibited significant redissolution, which was significantly suppressed by reducing sulfate concentration. This study provides valuable insights into managing complex pollution involving coexisting metalloids (Sb, As) and heavy metals (Pb, Cd, Cu, Zn).